Assay of methylglyoxal-derived protein and nucleotide AGEs. (20th March 2014) - Rabbani, Naila; Shaheen, Fozia; Anwar, Attia; Masania, Jinit; Thornalley, Paul J.
Abstract : Glyoxalase- and methylglyoxal-related research has required the development of quantitative and reliable techniques for the measurement of methylglyoxal-derived glycation adducts of protein and DNA. There are also other glycation adducts, oxidation adducts and nitration adducts of proteins and oxidation adducts of DNA. Proteolysis of protein releases glycation, oxidation and nitration free adducts (glycated, oxidized and nitrated amino acids) in plasma and nuclease digestion of DNA releases glycated and oxidized nucleosides into plasma and other body fluids for excretion in urine. The gold standard method for quantifying these adducts is stable isotopic dilution analysis LC–MS/MS. Protein and DNA adduct residues are determined by assay of enzymatic hydrolysates of protein and DNA extracts prepared using cocktails of proteases and nucleases respectively. Free adducts are determined by analysis of ultrafiltrates of plasma, urine and other physiological fluids. Protein damage markers (13 glycation adducts, five oxidation adducts and 3-nitrotyrosine) and DNA damage markers (three glycation adducts and one oxidation adduct) are quantified using 25 μg of protein, 10 μg of DNA or 5 μl of physiological fluid. Protein and nucleotide AGE (advanced glycation end-product) assay protocols resistant to interferences is described.